การศึกษาอัตรากำลังบุคคลทางการพยาบาลตามกิจกรรมการพยาบาลในหอผู้ป่วยหนักศัลยกรรมทั่วไป : กรณีศึกษาโรงพยาบาลมหาราชนครเชียงใหม่ - อภิรดี แสงศิริโรจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To determine the nursing staffing based on activities in surgical intensive care unit : a case study of Maharaj Nakorn Chiangmai Hospital. The research population consisted of 3 groups; critical patients, nursing care personnel, and nurse administrators. Ninety critical patients selected by simple random sampling from 3 categories according to severity of illness: closed observation, intensive nursing care, and intensive nursing and physician care. Nursing personnel consisted of 21 professional nurses, 9 practical nurses, and 4 nurse assistants. Research instruments developed by the researcher were; patient classification checklist, direct and indirect nursing care time checklist, and the questionnaire of the feasibility assessment. The major findings were as follows 1. The average nursing time required by critical patients in category 2, 3, 4 in 24 hour were 20.65, 24.93, and 35.68 hours, respectively. 2. The numbers of nursing personnel required in surgical intensive care unit based on nursing activities in Maharaj Nakorn Chaingmai Hospital were 27 professional nurses, 6 practical nurses, and 5 nurse assistants. After divided into shifts, there should be 8 professional nurses, 3 practical nurse, and 1 nurse assistant in the day shift, 6 professional nurses, 1 practical nurse, and 1 nurse assistant in the evening shift and the night shift. 3. The nurse administrators in this study agreed at the highest level in feasibility concerning the research applicability.